PSYCHOLOGICAL ASPECTS OF SPORTS INJURIES AMONG MALE PROFESSIONAL SOCCER PLAYERS IN CROATIA (Kinesiology, 2017)
The aim of this study was to assess occurrence of sports injuries among professional male soccer players in relation to their psychological characteristics. This prospective cohort study was conducted during the 2013/2014 sports season among all professional players with the first team contract in the first Croatian soccer league. A stratified sample of 182 male soccer players were selected for the assessment. They were surveyed during their preparation period before the beginning of the season and were under monitoring during the season. Seriousness of injuries was assessed depending on the duration (one day or more) of players’ non-participation in sports activities. Psychological characteristics were assessed by the General Anxiety Disorder Scale (GAD-7), Revised Center for Epidemiologic Studies Depression Scale, impulsive behaviour scale from the Zuckerman-Kuhlman Personality Questionnaire Cross-Cultural 50-item version and Psychological Skills Inventory for Sports. Majority of players (62.6%) experienced a kind of injury, with the mean number of 1.28 injuries per player, and 30.7% of them contracted severe injuries. Results of the binary regression model suggest that likelihood of being injured is mostly influenced by higher Impulsive Sensation Seeking and GAD-7 scores (OR=1.26 in both cases). In contrast, adequate mental preparation significantly lowers the chance of being injured (OR=0.89). The study gives an insight into proportions, severity, mechanisms and number of sport injuries in the population of Croatian professional soccer players. We propose several variables as important predictors of future injuries. Some scales, commonly used in this field, have been shown to be less useful for injury prediction.Key words: psychological characteristics, mental preparation, sports injuries, professional soccer players